Типы погребений кочевников XIII-XIV вв. Степного Приуралья - Матюшко, И.В. (Степи Европы в эпоху средневековья, 2010)
В результате исследования 319 погребений кочевников IX-XIV вв. Степного Приуралья1 было установлено, что основную часть фонда изученных захоронений (276 погребений или 86,5%) составляют погребения XIII-XIV веков. По классификации, основанной на данных о взаимовстречаемости признаков погребального обряда кочевников степей Приуралья IX-XIV вв., к золотоордынскому периоду были отнесены следующие типы погребений: захоронения под земляными насыпями с каменными кольцами или выкладками на древнем горизонте (тип ДП и тип ЕП); захоронения под земляными насыпями с сырцовыми оградками на древнем горизонте (тип EV); захоронения под чисто земляными насыпями (типы BI, Д1 и EI); погребения под каменными площадками (без земляной насыпи - тип EIV); захоронения под каменно-земляными насыпями (тип ЕIII); мавзолеи (тип EVI). The work analyzes finds of 276 burials of the 13th-14th centuries explored in the Steppe zone of the Ural region. The burials were divided typologically according to their type of over-grave constructions. Distinctions in the arrangement of over-grave constructions may be indicative of tribal peculiarities. Closely intertwined religious and social factors also influenced the type of over-grave constructions. In Golden Horde time there was a cult distinguished by burying skulls or separate bones of a horse (fragments of skulls, ribs) in graves. In other cases there were elements of a harness without horse bones in burials. There are also burials where parts o f a horse (a skull and legs) were buried above the deceased on a grave cover. Another kind of ceremony of burying a horse in Golden Horde time can be seen in burials with an entire horse skeleton placed on a step to the left of the dead. The fact of the presence of a horse may be accounted for by a high social rank of the deceased, whereas the way and place of burying a horse are connected with ethnic peculiarities.